2014
DOI: 10.1088/1674-1137/38/11/117005
|View full text |Cite
|
Sign up to set email alerts
|

Design of a 325 MHz SC Spoke040 cavity at IHEP

Abstract: The 325MHz, =0.40 superconducting single spoke cavity (Spoke040) was one of the most challenges for the China-ADS (Accelerator Driven System) project. The design was finished, and the fabrication was in progressing. In this paper, we studied the main radio frequency (RF) and mechanical parameters, and compared the arc-shaped and plate-shaped end group structures..

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…creep) are subjected to fracture, the study of metal behavior in the conditions of an external energy effect is necessary for analyzing their service lives. [1][2][3][4][5][6][7] In the last decade a lot of investigations were carried out and indicated that even a weak magnetic field (1 T) is able to change substantially the kinetic process, integral strength, and plastic characteristics of the solid body subjected to deformation. [8][9][10][11][12] It is conventional to relate the nature of this phenomenon to the spin conversion in impurity centers, which results in their electron structure transformation and corresponding decrease in their interaction with dislocations.…”
Section: Introductionmentioning
confidence: 99%
“…creep) are subjected to fracture, the study of metal behavior in the conditions of an external energy effect is necessary for analyzing their service lives. [1][2][3][4][5][6][7] In the last decade a lot of investigations were carried out and indicated that even a weak magnetic field (1 T) is able to change substantially the kinetic process, integral strength, and plastic characteristics of the solid body subjected to deformation. [8][9][10][11][12] It is conventional to relate the nature of this phenomenon to the spin conversion in impurity centers, which results in their electron structure transformation and corresponding decrease in their interaction with dislocations.…”
Section: Introductionmentioning
confidence: 99%